TINJAUAN HUKUM TERHADAP PERTIMBANGAN HAKIM DALAM PUTUSAN PERCERAIAN DI PERADILAN AGAMA. - Fadil Mas’ud; Baru, Maria Cindiany; Ortalana Anisa Merfi Tob; Sipriani Maria Dau; Mark Jhon Bilistolen; Dato Abdul Aziz (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Divorce cases in the Religious Courts in Indonesia continue to show a significant increase, indicating complex family law issues influenced by social, economic, and legal factors. This study aims to analyze the legal perspective on judges’ considerations in divorce decisions within the Religious Courts, focusing on how judges apply legal norms, factual evidence, and socio-legal considerations in adjudicating divorce cases. The research uses a normative legal method with a statutory approach and a conceptual approach, supported by secondary legal materials such as legislation, court decisions, journals, and relevant legal literature. The analysis is conducted descriptively and qualitatively to examine the consistency of judges’ reasoning in divorce rulings and their alignment with legal principles of justice, legal certainty, and utility. The findings show that judges’ considerations are not solely based on positive law, but also incorporate social conditions, psychological aspects of the parties, and the welfare of children affected by divorce. However, variations in judicial reasoning are still found in cases with similar characteristics, which may lead to disparities in decisions. These variations are influenced by judicial independence and differing interpretations of legal facts in court. The study concludes that judges’ considerations in divorce decisions reflect a balance between normative, sociological, and philosophical approaches, yet standardization is needed to ensure consistency and strengthen legal certainty in Religious Court decisions.